2012
DOI: 10.1002/lary.23429
|View full text |Cite
|
Sign up to set email alerts
|

Roles of IL‐17, Th1, and Tc1 cells in patients with IgG4‐related sclerosing sialadenitis

Abstract: Increases in Th1 and Tc1 cell populations and IL-17 expression might be involved in the mechanism of pathogenesis of IgG4-related sclerosing sialadenitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…9 They thus concluded that the pathogenesis of IgG4-RD might be mediated by a T H1 -predominant immune reaction. 810 Previous reports involved single-colour staining in the tissues from these patients, which would have been unable to distinguish CD4 + CTLs from T H1 cells. Some of these previous suggestions of T H1 cells in IgG4-RD may therefore have resulted from the erroneous categorisation of IFN-γ-secreting CD4 + CTLs as T H1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 They thus concluded that the pathogenesis of IgG4-RD might be mediated by a T H1 -predominant immune reaction. 810 Previous reports involved single-colour staining in the tissues from these patients, which would have been unable to distinguish CD4 + CTLs from T H1 cells. Some of these previous suggestions of T H1 cells in IgG4-RD may therefore have resulted from the erroneous categorisation of IFN-γ-secreting CD4 + CTLs as T H1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 Contrary to these results, some reports suggested that T H1 immune responses might play an important role in the pathogenesis of IgG4-RD. 810 However, these previous reports used single-colour staining of the tissues from these patients, which lacks the ability to directly identify T H1 or T H2 cells in disease tissues. Previous reports have all relied on indirect evidence to implicate CD4 + T cell subsets in this disease and more direct analyses of T cells have only recently been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…IgG4‐RD has various clinical manifestations, such as enlargement of the salivary and lacrimal glands, sclerosing pancreatitis, sclerosing cholangitis, tubulointerstitial nephritis, interstitial pneumonia, retroperitoneal fibrosis, inflammatory pseudotumor of the liver and lung, and inflammatory aortic aneurysm . In the head and neck, the submandibular gland is the most frequently involved site; here, the disease is also referred to as Küttner tumor or Mikulicz disease . Clinical manifestations are idiopathic, bilateral hard masses that are often misdiagnosed as tumors on the basis of their clinical and radiological features.…”
Section: Introductionmentioning
confidence: 99%
“…48 Th2 is known to promote fibrosis by stimulating fibroblasts, 49 and one hypothesis is that Th2 predominance is the central pathway of fibrotic organ damage in IgG4RD. However, Th1 predominance was also reported in 10 patients with IgG4-related sialadenitis, 50 and the numbers of regulatory T cells were also increased in peripheral blood from patients with AIP.…”
Section: Risk Factorsmentioning
confidence: 89%